1950
DOI: 10.1104/pp.25.1.150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on the Vitamin Content of Green Plants

Abstract: Change in the temperature with seasons is such an important factor in plant growth that its influence on the vitamin content of plants deserves a thorough investigation. Yet very few such investigations have been made and all but one of these have been concerned with ascorbic acid. One of the peculiarities of these investigations has been that they do not agree as to the effect of temperature on the concentration of ascorbic acid in plants. HAMNER et at. (5) found that tomato fruits produced at a temperature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1953
1953
1990
1990

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…The inhibition of vitamin » production is of interest with other studies which have shown that riboflavin content in tomato plants increases with high light intensity (3), long photoperiods (4), and high temperatures (5), factors which were not kept constant in these studies and which might have contributed to the variability of data observed.…”
Section: Resultsmentioning
confidence: 94%
“…The inhibition of vitamin » production is of interest with other studies which have shown that riboflavin content in tomato plants increases with high light intensity (3), long photoperiods (4), and high temperatures (5), factors which were not kept constant in these studies and which might have contributed to the variability of data observed.…”
Section: Resultsmentioning
confidence: 94%
“…Optimal temperatures for ascorbic acid accumulation tend to be under 20°C (Salunkhe and Desai 1988;Nagy and Wardowski 19881, although some notable exceptions such as turnip greens (Rosenfeld 1979) exist. Likewise, B-vitamins tend to accumulate better at 10-15°C in green vegetables but at 27-30°C in tomatoes (Gustafson 1950).…”
Section: Preharvest Conditionsmentioning
confidence: 97%
“…Likewise, B-vitamins tend to accumulate better at 10-15°C in green vegetables but at 27-30°C in tomatoes (Gustafson 1950).…”
Section: Preharvest Conditionsmentioning
confidence: 99%